2012
DOI: 10.4161/psb.20355
|View full text |Cite
|
Sign up to set email alerts
|

Copper-induced intracellular calcium release requires extracellular calcium entry and activation of L-type voltage-dependent calcium channels in Ulva compressa

Abstract: The marine alga Ulva compressa exposed to 10 mM copper showed a triphasic increase of intracellular calcium with maximal levels at 2, 3 and 12 h involving the activation of ryanodine-, Ins(1,4,5)P 3 -and NAADP-sensitive calcium channels. In order to analyze the requirement of extracellular calcium entry for intracellular calcium release as well as the activation of voltage-dependent calcium channels (VDCC) and phospholipase C, U. compressa was treated with EGTA, a non-permeable calcium chelating agent, with ve… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
19
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 19 publications
(21 citation statements)
references
References 23 publications
2
19
0
Order By: Relevance
“…However, in another study, copper excess rapidly increased in vivo DAG accumulation in roots of B. napus that could reflect PI-PLC activation [131]. Moreover, copper-induced release of intracellular calcium in marine alga Ulvia compressa seems to be dependent on PI-PLC activity [132].…”
Section: Heavy Metal Stressmentioning
confidence: 88%
“…However, in another study, copper excess rapidly increased in vivo DAG accumulation in roots of B. napus that could reflect PI-PLC activation [131]. Moreover, copper-induced release of intracellular calcium in marine alga Ulvia compressa seems to be dependent on PI-PLC activity [132].…”
Section: Heavy Metal Stressmentioning
confidence: 88%
“…As a secondary messenger of signal transduction within the cell of algae, Ca 2+ was closely related to stress adjustment mechanism of algae cell (Maksymiec 2007). Studies have shown that Ca 2+ permeable cationic channel of the algae had been affected by different types and concentrations of heavy metal ions (González et al 2012;Batistič and Kudla 2010). The reason for this may be that Ca 2+ combined with receptor within the algae to resist the low concentration heavy metal stress (Boyd 2010).…”
Section: Effects Of Cu 2+ and Zn 2+ On The Calcium Transduction Of CLmentioning
confidence: 96%
“…In marine algae, it has been shown that Ulva compressa (Chlorophyta) exposed to 10 M copper showed a triphasic increase of intracellular calcium with maximal levels (González et al 2012). As a secondary messenger of signal transduction within the cell of algae, Ca 2+ was closely related to stress adjustment mechanism of algae cell (Maksymiec 2007).…”
Section: Effects Of Cu 2+ and Zn 2+ On The Calcium Transduction Of CLmentioning
confidence: 99%
See 1 more Smart Citation
“…With respect to biochemical responses to Cu stress, the most comprehensive studies, to date, have been on the green seaweed Ulva compressa (Ulvophyceae) and brown seaweed Scytosiphon lomentaria (Phaeophyceae), two prominent members of the seaweed community in Cu-enriched coastal waters (over 1000 g L −1 ) of northern Chile (Lee and Correa, 2005;Ramirez et al, 2005). Chronic exposure of U. compressa to Cu induced an oxidative stress condition buffered mainly through the activation of the antioxidant enzyme APX, and synthesis of ASC whereas in S. lomentaria protection from oxidative stress occurs via increased activities of mainly CAT, GP and APX, and production of ASC (Contreras et al, 2005(Contreras et al, , 2009González et al, 2012b;Mellado et al, 2012;Ratkevicius et al, 2003). In both these species it was concluded that tolerance to Cu is a constitutive trait (Contreras et al, 2005;Ratkevicius et al, 2003).…”
Section: Introductionmentioning
confidence: 99%